CHINESE AND RUSSIAN LANGUAGE CULTURAL DIFFERENCES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
For a long time, China and Russia, taking into account their unique natural conditions, lifestyle, and the special role they played in socio-historical processes, created original models of cultural life. The habits and customs of people in any region or ethnic group to a certain extent reflect the habits and mentality of the whole nation. There are differences and similarities in the models of the cultural life of China and Russia. The comparative analysis makes it possible to compare the cultural specifics of two peoples. This article discusses the similarities and differences between China and Russia (from ancient times to the present) in religious culture, food culture, digital culture, and the culture of the holidays. Comparative analysis is also a means of forming tolerance in interethnic and intercultural interaction and promotes cooperative fruitful cooperation between the two neighbouring states. China and Russia play an important role in world history and culture. Despite the differences between languages, cultural practices, and cultural life in general, it can be considered that cultural identity is formed between two countries and between two civilizations, which is a strategic resource for the joint development of the two countries.